Circulating neutrophils activated by cancer cells and M2 macrophages promote gastric cancer progression during PD-1 antibody-based immunotherapy - Zhou, Chenfei; Guo, Liting; Cai, Qu; Xi, Wenqi; Yuan, Fei; Zhang, Huan; Yan, Chao; Huang, Lei; Zhu, Zhenggang; Zhang, Jun (Frontiers in Molecular Biosciences, 2023)
Aims To analyze correlation between neutrophil-to-lymphocyte ratio (NLR) and prognosis of advanced gastric cancer (AGC) patients treated by PD-1 antibody-based therapy, and to delineate molecular characteristics of circulating neutrophils by using single-cell RNA sequencing (scRNA-seq). Methods Clinicopathological information of 45 AGC patients treated by PD-1 antibody-based regimens at Department of Oncology, Ruijin Hospital was reviewed. Treatment outcomes including objective response rate (ORR), progressive-free survival (PFS) and overall survival (OS) were recorded. Correlation between NLR and efficacy of PD-1 antibody-based treatment was analyzed. Single-cell RNA sequencing (scRNA-seq) analysis was performed based on multi-site biopsy samples from two AGC patients to explore molecular characteristics of circulating neutrophils and its pro-tumor mechanisms. Tissue samples of 88 gastric cancer patients underwent radial gastrectomy were collected for immunochemistry staining. Results High posttreatment NLR was associated with poor outcomes of AGC patients treated by PD-1 antibody-based regimens. By using scRNA-seq analysis, increased number of circulating neutrophils were found in peripheral blood samples after treatment, in which neutrophils cluster 1 (NE-1) was the major subcluster. NE-1 was featured with neutrophil activation phenotype with high expression of MMP9, S100A8, S100A9, PORK2, and TGF-β1. NE-1 displayed an intermediate state in pseudotime trajectory analysis with gene function enrichment of neutrophil activation, leukocyte chemotaxis and negative regulation of MAP kinase activity. By cellular interaction analysis, chemokine signaling pathway is the major interactional pathway of NE-1 between subclusters of malignant epithelial cells (EP-4) as well as M2 macrophages (M2-1, M2-2). In return, MAPK signaling pathway and Jak-STAT signaling pathway of EP-4, including IL1B/IL1RAP, OSM/OSMR and TGFB1/TGFBR2 axes, were identified interacting between EP-4 and NE-1. High expression of OSMR in tumor cells was closely correlated with lymph nodes metastasis of gastric cancer. Conclusions Posttreatment NLR could be a poor prognostic marker of AGC patients treated by ICIs. Subcluster of circulating neutrophils activated by tumor cells and M2 macrophages could participate in gastric cancer progression through signaling interaction with tumor cells.